New insights into the distribution of APOE polymorphism in the Iberian Peninsula. The case of Andalusia (Spain). (September 2014) - Reales, Guillermo; Hernández, Candela L.; Dugoujon, Jean-Michel; Novelletto, Andrea; Cuesta, Pedro; Fortes-Lima, César; Rodríguez, Juan N.; Calderón, Rosario
Abstract Background: The APOE gene has received much attention due to the remarkable spatial variation patterns of some of its genotypes and alleles in human populations and to its relevance in biomedicine. Aim: This work was addressed to investigate the extent of APOE polymorphism between autochthonous Andalusians originating from Huelva and Granada provinces. No data on this marker in these southern Spanish coastal populations are available up to date. Subjects and methods: This study used genomic DNA from healthy, unrelated Andalusians of both sexes (n = 322). All samples were genotyped for two SNPs, rs429358 and rs7412, which determine the three APOE alleles: ε2, ε3 and ε4. For analyses, a TaqMan-based technique was applied using a RT-PCR. Comparisons with other Mediterranean populations were performed based on multivariate analysis. Results: A relatively high frequency of ε4 in Granada (eastern Andalusia), as well as a low ε2 frequency in Huelva (western Andalusia) were observed. The finding that ε4 allele in Southern Spain and Portugal is higher than expected given its geographical location poses an interesting question for this study, given the well-established APOE-ε4 gradient in Europe. Conclusion: This population study may represent useful information for further prospective anthropological and molecular genetic studies focused on unravelling the relationship between population genetic composition and specific human diseases.